The changing role of capital in the US private business sector: evidence for a new economy - Gordon C. Bjork (Claremont McKenna College, Department of Economics, 2003)
Economists differ in their explanation of changes in the rate of U.S.economic growth in the latter half of the 20th century-particularly for the new economy period from 1982-2000. Adherents of the Neoclassical Growth Model have emphasized that with the increase in the capital/labor ratio the aggregate production function would be subject to diminishing returns so that economies would asymptotically approach a steady state in terms of output per worker and output per unit of capital. Endogenous Growth theorists have emphasized upward shifts in production functions offsetting diminishing returns. Both theories have neglected to incorporate into their growth models the effects of systematic shifts in the composition of output that accompany economic growth. The paper analyzes the Private Business Sector (exclusion of Government, Residential Housing, and Not For Profit), uses a more restrictive measure of output, Net National Income, rather than Gross Domestic Product and a more general measure of labor input, Persons Engaged in Production, rather than Full Time Equivalent Employment or labor hours in analysis. Using BEA data sets for the stock of physical capital and gross product originating by SIC sector and industry, the paper demonstrates that about half the increase in labor and capital productivity in the new economy has been the result of endogenous growth within sectors and industries and the other half is attributable to shifts in the composition of output away from more physical capital-intensive industries to more labor-intensive industries. After falling steadily from 1966 to 1982, both the nominal output/capital (Y/C) and real output/capital ((Q/K) ratios rise steadily from 1982 to 2000. Growth in the real capital/labor (K/N) ratio slows during this period so that in marked contrast to earlier periods, half of the growth in real output per worker (Q/N) is attributable to increases in capital productivity. Increase in the Y/C ratio is shown, by counterfactual analysis, to depend partly on the shift of output from more to less capital intensive industries. The paper also demonstrates that half of the change in the nominal Y/C ratio is due to real rather than relative price changes and that changes in capacity utilization over the business cycle explain only a negligible part of the increase.
Keywords: 330; Wirtschaftswachstum; Produktionsfunktion; Privatwirtschaft; Produktivität; USA; New Economy